An experimental investigation on concomitant Vortex-Induced Vibration and axial top-motion excitation with a long flexible cylinder in vertical configuration. (15th May 2018) - Franzini, G.R.; Pesce, C.P.; Gonçalves, R.T.; Fujarra, A.L.C.; Mendes, P.
Abstract: An experimental investigation of concomitant Vortex-Induced Vibration (VIV) and top-motion excitation with a long and vertical flexible cylinder is presented. Underwater optical instrumentation allows to directly measure the cartesian coordinates of 43 targets placed along the model. Standard analyses, based on statistical evaluation of local displacement time-histories and on spectral analysis, are carried out. Additionally to the standard approach, modal decomposition is adopted, allowing to obtain modal-amplitude time-histories. It was found that the concomitant VIV and top-motion excitation significantly affects the flexible cylinder response when compared to the pure VIV tests. When the top-motion excitation has frequency twice the first natural frequency in still water ( f t : f N, 1 = 2 : 1 ), parametric instability of the first vibration mode occurs concomitant to VIV phenomenon. Such instability leads to a marked increase in the oscillation amplitudes for the whole range of towing speed tested. Highlights: Concomitant Vortex-Induced Vibrations and axial top-motion excita-tion. Instantaneous deformed con_guration determined in time through im-age tracking technique. Enhancement of VIV oscillations caused by parametric instability. Top-motion excitation lead to signi_cant modi_cations in the ampli-tude spectra and in the modal amplitude time-histories.